2019
DOI: 10.3390/w11071355
|View full text |Cite
|
Sign up to set email alerts
|

New Insights of the Sicily Channel and Southern Tyrrhenian Sea Variability

Abstract: The dynamics of the Sicily Channel and the southern Tyrrhenian Sea are highly influenced by the seasonal variability of the Mediterranean basin-wide circulation, by the interannual variability of the numerous mesoscale structures present in the Channel, and by the decadal variability of the adjacent Ionian Sea. In the present study, all these aspects are investigated using in-situ (Lagrangian drifter trajectories and Argo float profiles) and satellite data (Absolute Dynamic Topography, Sea Level Anomaly, Sea S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 30 publications
0
23
0
Order By: Relevance
“…In spring we identify some of the winter structures indicated in Jouini et al [3] and Menna et al [4,5] like the ATC, BAC, MCC, MG, MSG, MRV and the PV as shown in Figure 4b. The ATC flows towards Sicily where two gyres are detached, the cyclonic MG and the anticyclonic MCC circling around Linosa island, most likely due to the influence of the LT at 36°N.…”
Section: Mean Surface Circulation the Sicily Channelmentioning
confidence: 63%
See 2 more Smart Citations
“…In spring we identify some of the winter structures indicated in Jouini et al [3] and Menna et al [4,5] like the ATC, BAC, MCC, MG, MSG, MRV and the PV as shown in Figure 4b. The ATC flows towards Sicily where two gyres are detached, the cyclonic MG and the anticyclonic MCC circling around Linosa island, most likely due to the influence of the LT at 36°N.…”
Section: Mean Surface Circulation the Sicily Channelmentioning
confidence: 63%
“…Due to baroclinic instabilities, the Atlantic current (AC) regularly forms meanders that eventually detach from the current and become either cyclonic or anticyclonic eddies [36] like the ones observed by Jouini et al [3] and Jebri et al [37,38]. Figure 3 shows the SC inter-annual geostrophic circulation derived from the ADT data depicting some of the AC-born structures described in Jouini et al [3] and Menna et al [5] such as the cyclonic Medina Gyre (MG), the cyclonic Messina Rise Vortex (MRV), the anticyclonic Pantelleria Vortex (PV, which in the literature is mentioned as cyclonic), the anticyclonic MSG, the AIS, the Bifurcation Atlantic Current (BAC) and the Atlantic Tunisian Current (ATC). From ADT and SGV, the MSG shows a seasonal semi-permanent behavior and contributes to the channel's circulation along with the AIS.…”
Section: Mean Surface Circulation the Sicily Channelmentioning
confidence: 76%
See 1 more Smart Citation
“…A combined use of satellite measurement data and Hybrid Coordinate Ocean Model (HYCOM) reanalysis data, together with the self-organizing map (SOM) method, was used to investigate the east branch of the Kuroshio bifurcation where four coherent patterns associated with mesoscale eddies in the Pacific Ocean were found [4]. On the other hand, generation mechanisms like wind curl and dense water flow of the mesoscale eddies in the Ionian Sea (central Mediterranean) were addressed and some comparisons between the two forcing mechanisms were discussed in the paper by Menna et al [5]. The Sicily Channel, in between the eastern and western Mediterranean basins, is another area characterized by large mesoscale variability and water mass exchanges that was analyzed in the paper by Reyez-Suarez et al [6].…”
Section: Oceanic Circulation and Mesoscale Features: Experimental Andmentioning
confidence: 99%
“…Geostrophic flow obtained from the altimetry data fits very well with the HF radar data averaged over a few weeks. The paper presented by Menna et al [5] deals with such variability more or less in the same area using a combination of long-term, time-series altimetry data, Sea Surface Temperature (SST), and remotely sensed wind data in order to study the seasonal and multiannual variability of mesoscale structures. Wind data allowed the authors to discuss in detail the generation mechanism of mesoscale eddies and the importance of wind stress and wind stress vorticity fields on their seasonal variability.…”
Section: Oceanic Circulation and Mesoscale Features: Experimental Andmentioning
confidence: 99%